Composite sliding-mode consensus algorithms for higher-order multi-agent systems subject to disturbances - Wang, Xiangyu; Wang, Guodong; Li, Shihua; Lu, Kunfeng (IET control theory & applications, 2020)
Consensus problems for both leaderless and leader-follower disturbed higher-order multi-agent systems are investigated in this study. Based on the combination of integral sliding-mode control and disturbance observer techniques, composite sliding-mode consensus protocols are proposed for leaderless and leader-follower disturbed multi-agent systems, respectively. First, for the leaderless case, composite sliding-mode consensus protocols are designed to make the agents achieve asymptotic consensus. Second, for the leader-follower case, finite-time composite sliding-mode consensus protocols are presented to make the followers achieve consensus with the leader in finite time. Then based on the consensus algorithms proposed in this study, a consensus control strategy is given to realise the velocity and altitude finite-time consensus for a class of leader-follower multi-hypersonic vehicle systems. Finally, the numerical simulations are conducted to validate the efficiency of the proposed consensus algorithms.